Great religions of the world - Nolan, Mary Lee; Educational Video Network, Inc. (Virginia : Educational Video Network, 1995)
Looks at the major religions of the world and the common aspects of belief systems.
Videography, Mary Lee Nolan, Sidney Nolan ; video editor, Brian Kaspar ; narrator, Thomas F. Soare.
Students
Keywords: Religions